Review: Methods for Enhancing Solubility of Carvedilol - Iyan Sopyan; Rania Talinta L; Nurdiani Adiningsih; Norisca Aliza Putriana; Sandra Megantara2 Megantara (Indonesian Journal of Pharmaceutics, 2022)
The oral route of administration is the most frequently used route of drug administration and is generally the most convenient for patients. For an oral drug to be effective, a therapeutic concentration in the blood must be achieved. Solubility in water and permeability of active pharmaceutical ingredients are often used as the main conditions for rapid and complete absorption and high bioavailability. Carvedilol is beta blockers that works as an antihypertensive drug and included in biopharmaceutical classification system (BCS) class II with high permeability but low solubility. Due to this, the goal of this review is to go through a few different methods for increasing solubility of carvedilol. dissolution, and bioavailability. Various solubility enhancement techniques have been applied to carvedilol, including co-crystallization, liquidsolid technique, cyclodextrin inclusion complex, nanoparticles, hydrotrophy, nanosuspension, solid dispersion, nanoemulsion, and dendrimers. These techniques have been shown to increase the solubility and dissolution rate of carvedilol thereby increasing its bioavailability.Keyword: carvedilol, solubility enhancement, BCS class II